2000
DOI: 10.1038/35035089
|View full text |Cite
|
Sign up to set email alerts
|

An SNP map of human chromosome 22

Abstract: The human genome sequence will provide a reference for measuring DNA sequence variation in human populations. Sequence variants are responsible for the genetic component of individuality, including complex characteristics such as disease susceptibility and drug response. Most sequence variants are single nucleotide polymorphisms (SNPs), where two alternate bases occur at one position. Comparison of any two genomes reveals around 1 SNP per kilobase. A sufficiently dense map of SNPs would allow the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(71 citation statements)
references
References 25 publications
0
71
0
Order By: Relevance
“…SNPs have been identified in specific genes (Nickerson et al 1998;Rieder et al 1999;Taillon-Miller et al 1999;TaillonMiller and Kwok 2000), on whole chromosomes (Mullikin et al 2000;Dawson et al 2001), and throughout the human genome (Altshuler 2000;The International SNP Map Working Group 2001). Most recently, the International HapMap project has completed an extensive SNP discovery effort to further increase the density of SNPs across the human genome (The International HapMap Consortium 2003).…”
mentioning
confidence: 99%
“…SNPs have been identified in specific genes (Nickerson et al 1998;Rieder et al 1999;Taillon-Miller et al 1999;TaillonMiller and Kwok 2000), on whole chromosomes (Mullikin et al 2000;Dawson et al 2001), and throughout the human genome (Altshuler 2000;The International SNP Map Working Group 2001). Most recently, the International HapMap project has completed an extensive SNP discovery effort to further increase the density of SNPs across the human genome (The International HapMap Consortium 2003).…”
mentioning
confidence: 99%
“…To date, the number of publicly available single-nucleotide polymorphisms (SNPs) well exceeds two million (dbSNP build 105). The main data sources for computational SNP discovery have been expressed sequence tags (ESTs) (1,2), genomic restriction fragments (3), sequences aligned to genome both from the ends of bacterial artificial chromosomes (BACs) and from random shotgun sequences of clone sequence, and overlapping regions of genomic clone sequences themselves (4,5). Generally, SNPs from these data were detected in surveys of a few chromosomes, an ascertainment strategy that biases allele frequency patterns toward common variations (6), and thus these data are expected to fall into a range that is unlikely to contain the majority of clinically important mutations (7,8).…”
mentioning
confidence: 99%
“…III). In human SNP screening studies, the SNP density reported is much lower, and one SNP is reported to occur in every 1000-2000 bases when two human chromosomes are compared [2,23,28]. Another study analysing SNP incidence in 106 human genes, provided a higher density of one SNP per 348 bp, and their θ values of synonymous and non-synonymous SNP in coding regions were 1.0 × 10 −3 and 1.96 × 10 −4 when corrected for sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, several high resolution SNP maps have been created for several chromosomes or even the whole genome, providing useful resources for studies on haplotypes associated with human diseases [2,23,28]. Furthermore, an SNP map of porcine chromosome 2 has been reported [18], however such studies have not been performed in the chicken yet.…”
Section: Introductionmentioning
confidence: 99%